An HMD-based pedestrian simulator for training and measuring individuals perceptual-motor behaviour in road crossing. (5th January 2021) - Azam, Muhammad; Choi, Gyoojae; Chung, Hyun Chae
Pedestrian simulators are used to evaluate human perception and behaviour in road-crossing. It is, however, needful to ensure that whether the virtual environment used in those systems is in accordance with real-world situations and ecologically validated. The purpose of this paper is to present an overview of a simulator that can be used to study pedestrians' perceptual-motor behaviour in road crossing. Depending on the perception-action approach, we developed a user-friendly experimental paradigm in which a participant can perceive/walk to cross the road. The paradigm consisted of a mobile virtual reality, an actual corridor, and a locomotion recording system. A summary of results relating to improved perceptual judgment and movement timing has been presented to validate the applicability of this pedestrian simulator in research. The summary of the results concluded that this innovative pedestrian simulator is a beneficial tool for research and training to improve pedestrians' perceptual-motor behaviour in the road-crossing task.